Design and Development Towards a Novel Prosthesis for Total Shoulder Arthroplasty to Reduce Aseptic Glenoid Loosening - Dey, Roopam (Department of Human Biology, 2022)
Total shoulder arthroplasty (TSA) is the most common surgical solution, that helps in restoring the structural and functional integrity of a diseased glenohumeral (GH) joint with intact rotator-cuff. A 300% increase in the usage of TSA has been observed since 2007, along with 2.5% increase in revision rate. Aseptic glenoid loosening accounts for 37% of postsurgical failures in TSA. Eccentric loading of the prosthetic glenoid cup, leading to the “rocking horse” effect, is one of the prevalent causes of aseptic glenoid loosening. Current anatomical total shoulder prosthesis (ATSP) geometry does not consider all the GH morphometric features, for example the elliptical shape of the humeral head. Moreover, the morphometric studies leading to the initial ATSP design did not consider the GH morphology of any sub-Saharan population. Hence, there exists a gap in understanding of the implications of certain morphometric features on the functionality of a post-TSA GH joint. This thesis had two primary aims to address this gap in knowledge. Firstly, to study the GH morphometric variations between cohorts representing native European (Swiss) and native sub-Saharan (South African) populations. Secondly, to develop anatomically inspired ATSP design concepts and test them using biomechanical and finite element (FE) models, insilico, under standardised testing protocols. The morphometric analysis suggested that an average Swiss humeral head radius of curvature was larger (P<0.05) than the average South African humeral head. By comparing the biological head sizes, across both the populations, with the dimensions of the commercially available humeral heads, it can be inferred that suitable humeral prostheses are currently not available for individuals with head sizes >28mm or <19mm. Considering both the populations, the inherent shape of an average humeral head was found to be elliptical. The thickest region of the head was found to lie in the posterior region and not at the geometric center. Hertzian contact theory was applied to calculate the GH stresses produced by symmetric and asymmetric elliptical heads. Higher concentric stresses (P<0.001), within the acceptable limit for polyethylene, were observed to be imparted by the asymmetric heads. Population-specific musculoskeletal models were developed to study the post-TSA kinematic variation. When an identical range of motion (RoM) was performed by these models, population-specific variation in muscle moment arms was observed. The novel glenoid designs were not found to alter the post-surgical kinematics. FE models of the biradial, compartmental and pear-shaped glenoid implant designs were subjected to compressive and shear loading according to the American Society for Testing and Materials (ASTM). Using the bi-radial the glenoid cup, with thickened posterior-superior surface, anatomically relevant force distribution patterns could be replicated. Compartmentalising the glenoid prosthesis into concentric and eccentric regions with the gaps, proved to be highly beneficial. When compared to a commercially available glenoid prosthesis, the compartmental prosthesis was able to contain the GH forces to the concentric region for longer, delaying the eccentric loading and therefore potentially reducing the “rocking horse” effect. In the light of the above observations, two conclusions can be drawn from this thesis. Firstly, it would be beneficial if population-specific ATSP were made available for natives of certain geographic locations. Secondly, glenoid prosthesis designs could be compartmentalised to contain the GH joint forces within the concentric regions of the cup which might aid in the reduction of post-TSA complications.